1999
DOI: 10.1515/jpem.1999.12.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Microvascular and Neurologic Abnormalities in a Population of Diabetic Children

Abstract: One hundred and twenty-nine (87%) of a total county population of 150 eligible diabetic children together with 144 age- and sex-matched control children participated in a longitudinal, epidemiological study of the evolution of diabetic microvascular disease. At enrollment the median (range) age of the diabetic children was 12.5 (3.7-16.8) years with a median diabetes duration of 2.9 (0.1-13.4) years and a median HbAl of 11.1 (6.8-17.9)%. Two sets of measurements were made over a period of 18 months for all ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…Diabetic patients with a history of poor glycemic control Long-term poor glycemic control can only increase the risk of developing advanced diabetic neuropathy, although long-term follow-up studies are lacking (117). Mustonen et al (173) showed in a 4-year follow-up study of 32 individuals with type 2 diabetes that poor glycemic control was an important determinant of the progression of autonomic nerve dysfunction.…”
Section: Who Is a Candidate For Testing?mentioning
confidence: 99%
“…Diabetic patients with a history of poor glycemic control Long-term poor glycemic control can only increase the risk of developing advanced diabetic neuropathy, although long-term follow-up studies are lacking (117). Mustonen et al (173) showed in a 4-year follow-up study of 32 individuals with type 2 diabetes that poor glycemic control was an important determinant of the progression of autonomic nerve dysfunction.…”
Section: Who Is a Candidate For Testing?mentioning
confidence: 99%
“…49 -53 • Poor glycemic control plays a central role in development and progression. 49,54 • Intensive therapy can slow the progression and delay the appearance of abnormal autonomic function tests. 55 • Subclinical autonomic neuropathy can be detected early using autonomic function tests.…”
Section: Progression Of Canmentioning
confidence: 99%
“…Subsequent studies reported variable rates of DN among children with T1D, ranging from 22% (Kaar et al, 1983), 57% (Hyllienmark et al, 1995), 87% (Meh and Denislic, 1998), to 97% (Karsidag et al, 2005). The presence of diabetic autonomic neuropathy is likely underestimated owing to suboptimal screening, and subclinical diabetic autonomic neuropathy has been reported to be between 8% and 75% in children with T1D (Karavanaki and Baum, 1999;Verrotti et al, 2009) (see Table 10.2). DN is also an early complication of T2D (Karabouta et al, 2008); however, the prevalence data on neuropathy in pediatric T2D are currently limited.…”
Section: Definitionmentioning
confidence: 99%
“…Autonomic neuropathy may be present early in childhood (Lucini et al, 2009), independent of the duration of diabetes or the degree of glycemic control (Verrotti et al, 1995;Karavanaki and Baum, 1999). In studies using pupillary constriction as a marker of autonomic function, Schwingshandl found that 142 adolescents with T1D had smaller resting pupil diameter than 75 controls; abnormal pupillary response correlated with higher hemoglobin AIc (HbA1c), longer duration of diabetes, and presence of diabetic retinopathy (Schwingshandl et al, 1993).…”
Section: Autonomic Function Testmentioning
confidence: 99%